Cyclone Idai shows why long-term disaster resilience is so crucial - Arndt, Channing; Ringler, Claudia (2019)
Cyclone Idai struck Beira, the fourth largest city in Mozambique, in mid-March with torrential rains and winds of more than 190 km per hour. It took days for the sheer size of the resulting disaster to be understood. Dramatic pictures and video showed that the cyclone had left behind an inland sea up to 6 meters deep. Hundreds of people died in the storm and its immediate aftermath, and millions will be affected, potentially for years to come. Increases in the frequency and intensity of extreme weather events, such as Cyclone Idai, are increasingly viewed as a consequence of climate change. This is true globally, but particularly for areas like southern Africa. Climate related disasters harm growth and development prospects. Climate change, with its more extreme weather events and rising seas, will both broaden and intensify these impacts on poor communities – and entire countries. Poor people in poor countries are most vulnerable to disasters such as Cyclone Idai.